2019
DOI: 10.1177/0308575919884883
|View full text |Cite
|
Sign up to set email alerts
|

The development of DDP-informed parenting groups for parents and carers of children looked after or adopted from care

Abstract: This article describes the development of two parenting groups -Nurturing Attachments (Golding, 2014) and Foundations for Attachment (Golding, 2017). Both programmes are informed by the Dyadic Developmental Psychotherapy (DDP) model developed by Dan Hughes in the USA (Hughes, 2011;Hughes, Golding and Hudson, 2019). The groups were devised to provide much needed support for foster, residential and kinship carers and adopters parenting children and young people of all ages. Participants express high satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Despite the useful findings of the service evaluation, it should be recognised that some limitations were evident. Principally, this was apparent when interviewing the foster carers, as a large proportion had accessed the Fostering Lasting Attachments Group (FLAG; Golding, 2006), with only some having attended additional or alternative training (all of which had occurred in person). As a consequence, some participants found it difficult to recall the exact content of consultations, which may have affected the answers they were able to give.…”
Section: Limitationsmentioning
confidence: 99%
“…Despite the useful findings of the service evaluation, it should be recognised that some limitations were evident. Principally, this was apparent when interviewing the foster carers, as a large proportion had accessed the Fostering Lasting Attachments Group (FLAG; Golding, 2006), with only some having attended additional or alternative training (all of which had occurred in person). As a consequence, some participants found it difficult to recall the exact content of consultations, which may have affected the answers they were able to give.…”
Section: Limitationsmentioning
confidence: 99%
“…In a longitudinal case study over a ten-year period, positive outcomes were reported for a child with autism when a PBS approach was utilized ( Lucyshyn et al, 2007 ). There is some evidence for positive outcomes of interventions delivered ‘by proxy’ to parents/carers of children with trauma ( Golding, 2019 ) and anxiety ( Lebowitz et al, 2020 ). The Preschool Autism Communication Trial (PACT) demonstrates long-term symptom reduction in autistic children following a parent-mediated early intervention ( Pickles et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%